Zapisz w postaci potęgi podaną sumę;
a) a²+2ab+b²
b) a²+20ab+100b²
c) 100a²+80ab+16b²
d) 9a²+54ab+81b²
e) 16a²+8ab+b²
f) a²+24a+36
g) a²-4ab+4b²
h) 100a²-180ab+81b²
i) 0,25a²-10ab+100b²
j) 9a²-30ab+25b²
k) 36a²-24ab+4b²
l) 9a²-36a+36

3

Odpowiedzi

2009-12-16T22:14:50+01:00
A) a²+2ab+b² = (a+b)^2
b) a²+20ab+100b² = (a+10b)²
c) 100a²+80ab+16b² = (10a+8b)²
d) 9a²+54ab+81b² (3a+9b)²
e) 16a²+8ab+b² = (4a+b)²
f) a²+24a+36 (a+6b)²
g) a²-4ab+4b² = (a-2b)²
h) 100a²-180ab+81b² = (10a-9b)²
i) 0,25a²-10ab+100b² = (0,5a-10b)²
j) 9a²-30ab+25b² = (3a-5b)²
k) 36a²-24ab+4b² = (6a-2b)²
l) 9a²-36a+36 = (3a-6)²
3 5 3
2009-12-16T22:15:21+01:00
Dopisz potęgę 2.
a) (a+b)
b) (a+10b)
c) (10a+4b)
d) (3a+9b)
e) (4a+b)
f)
g) (a-2b)
h) (10a-9b)
i)
j) (3a-5b)
k) (6a-2b)
l) (3a-6)
1 5 1
Najlepsza Odpowiedź!
2009-12-16T22:16:51+01:00
A) a²+2ab+b² = (a+b)²
b) a²+20ab+100b² = (a+10b)²
c) 100a²+80ab+16b² = (10a+4b)²
d) 9a²+54ab+81b² = (3a+9b)²
e) 16a²+8ab+b² = (4a+b)²
f) a²+24a+36 = (a+6)² // ten przykład jest chyba źle przepisany
g) a²-4ab+4b² = (a-2b)²
h) 100a²-180ab+81b² = (10a-9b)²
i) 0,25a²-10ab+100b² = (0.5a-10b)²
j) 9a²-30ab+25b² = (3a-5b)²
k) 36a²-24ab+4b² = (6a-2b)²
l) 9a²-36a+36 = (3a-6)²
1 5 1